2000
DOI: 10.1159/000007733
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mitogen-Activated Protein Kinase Activities Stimulated with Interleukin-1-Beta and Mechanism(s) of the Kinase Signaling Pathways in Rat Gastric Epithelial Cells

Abstract: Interleukin (IL)-1β, a multifunctional cytokine, is associated with inflammatory gastric mucosa, but the responses of gastric epithelial cells stimulated by IL-1β are not known. We determined whether IL-1β activates the two subfamilies of mitogen-activated protein (MAP) kinases, extracellular signal-regulated kinases (ERKs) and c-Jun NH2-terminal kinases (JNKs), in rat gastric epithelial cells (RGM1) using in-gel kinase assays. In addition, we examined the mechanism(s) underlying their signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…5 and 6, IL-1β induced phosphorylation of ERK, and this was inhibited specifically by PD98059. These results are consistent with those reported in other cell types (Beales, 2002;Tominaga et al, 2000;Yang et al, 2000;Zhai et al, 2004). In addition, IL-1β-induced phosphorylation of ERK was completely inhibited by IL-1ra and AG1478 (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…5 and 6, IL-1β induced phosphorylation of ERK, and this was inhibited specifically by PD98059. These results are consistent with those reported in other cell types (Beales, 2002;Tominaga et al, 2000;Yang et al, 2000;Zhai et al, 2004). In addition, IL-1β-induced phosphorylation of ERK was completely inhibited by IL-1ra and AG1478 (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that activation of the ERK pathway is important in mediating the growth stimulatory actions of IL-1β. Activation of MAP kinase cascades, including the p42 and p44 ERK pathways and p46JNK and p55JNK c-Jun NH 2 -terminal kinases by IL-1β has been demonstrated in rat gastric epithelial cells [41,42], but the functional importance of these pathways was not examined. Activation of ERKs and JNKs was inhibited by genistein [41], consistent with the inference of the current study that MAPKs lie downstream of tyrosine activity in IL-1β-induced signalling.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that IL-1ß induces MAPK activation, including extracellular signal-regulated kinases (ERK), JNK, and p38 MAPK, in normal rat gastric epithelial cells (RGMI cells) and weakly inhibits cell proliferation (20). In contrast, serum stimulation (2%) induces phosphorylated-ERK, -JNK, and -p38 MAPK as well as the expression of cyclooxygenase-2, a potent proliferative factor for gastrointestinal normal and cancer cells, in MKN 45 cells (gastric cancer cell line) and HT-29 cells (21).…”
Section: Discussionmentioning
confidence: 99%